George and The Knight - Mcmillan, Sue and Jenkins, Ellie (London Far Far Away Books, 2012)
George isn't an average dragon. In fact he's so mild-mannered that the rest of his colony disown him until he can prove himself worthy. When he meets Alric, it seems George has found his place - until Lord Halagad arrives and threatens the whole village. Can George rise to the challenge and save his friends?
Include Colour Illustrations
Keywords: Courage -- Dragons